Learning the "language of connections". The value of art in the thinking of Gregory Bateson - Silvia Demozzi (Firenze University Press, 2015)
The article presents a brief analysis of the role of art in the thinking of Gregory Bateson. This is the starting point for a pedagogical reflection that may emphasize, in the educational processes, the languages of connection, typical of art and metaphor, and may propose alternative paths to «single thought» and simplification.